2022
DOI: 10.54093/bmra.v1i1.2121
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Leadership and Organizational Commitment in Faith-Based Healthcare Organizations

Abstract: In response to increasing cultural diversity at faith-based healthcare organizations, sincere, responsive, and sensitive leadership is critical to ensuring the organizational commitment of African American employees. Research was lacking on the relationship between toxic leadership and organizational commitment within faith-based healthcare settings. Further, little research existed on the ways toxic leadership affects the organizational commitment of African American workers. The purpose of this quantitative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the study by Atalla and Hassan Mostafa (2023), nurses exposed to a toxic leader reported an overall reduction in the composite organizational commitment scores. In two separate studies, toxic leadership was associated with a significant reduction in affective (Abou Ramadan and Eid, 2020), normative (Abou Ramadan and Eid, 2020) and continuance commitment (Honer and Burchell, 2022). Organizational justice and organizational trust were outcomes tested in three studies.…”
Section: Major Findings Toxic Leadership Outcomesmentioning
confidence: 99%
“…In the study by Atalla and Hassan Mostafa (2023), nurses exposed to a toxic leader reported an overall reduction in the composite organizational commitment scores. In two separate studies, toxic leadership was associated with a significant reduction in affective (Abou Ramadan and Eid, 2020), normative (Abou Ramadan and Eid, 2020) and continuance commitment (Honer and Burchell, 2022). Organizational justice and organizational trust were outcomes tested in three studies.…”
Section: Major Findings Toxic Leadership Outcomesmentioning
confidence: 99%